Secure and verifiable outsourcing of Euclidean distance and closest pair of points with single untrusted cloud server. Issue 1 (21st March 2023) - Prasad, Shilpee; Purushothama, B.R.
Owing to resource constraints, often, a client has to outsource the computation to the untrusted cloud service provider. As cloud service providers are often untrusted, the computation's result should be verified for correctness. Also, the cost of verification should be less than the cost of actual computation. In this paper, we address the problem of verifying the computation of a geometric problem. In particular, we address the problem of verifying the Euclidean distance and closest pair of points returned by the single untrusted cloud service provider. We have designed verification schemes for outsourcing Euclidean distance and the closest pair of points. We have proved that the proposed scheme has negligible server cheating probability. Also, the scheme preserves the privacy of the outsourced data. We have implemented the closest pair of points verification scheme and show that the verification cost is significantly less than the actual computation cost. Also, compared to the existing scheme, the proposed scheme has less server cheating probability.